2004
DOI: 10.1038/sj.onc.1207012
|View full text |Cite
|
Sign up to set email alerts
|

Homo- and hetero-oligomerization of PDZ-RhoGEF, LARG and p115RhoGEF by their C-terminal region regulates their in vivo Rho GEF activity and transforming potential

Abstract: PDZ-RhoGEF, LARG, and p115RhoGEF are members of a newly identified family of Rho-guanine nucleotide exchange factors (GEFs) exhibiting a unique structural feature consisting of the presence of an area of similarity to regulators of G protein signaling (RGS). This RGS-like (RGL) domain provides a functional motif by which Ga 12 and Ga 13 can bind and regulate the activity of these RhoGEFs, thus providing a direct link from these heterotrimeric G proteins to Rho. PDZ-RhoGEF and LARG can also be phosphorylated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 36 publications
8
99
1
Order By: Relevance
“…It was recently shown that Fyn may stimulate LARG activity downstream of integrins (Guilluy et al, 2011), but we observe, rather, an inhibition of Src family kinases upon loss of CD98hc in our experimental model, which suggests that LARG has to be activated by other means. These may possibly include phosphorylation by kinases such as PKC or FAK, for instance (Chikumi et al, 2002;Disatnik et al, 2002;Suzuki et al, 2003;Dovas et al, 2006), as well as regulation of LARG homodimerization by CD98hc, which has long been known to regulate its activity (Chikumi et al, 2004). Further molecular investigations, in vitro, in cell culture should be performed to dissect this regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that Fyn may stimulate LARG activity downstream of integrins (Guilluy et al, 2011), but we observe, rather, an inhibition of Src family kinases upon loss of CD98hc in our experimental model, which suggests that LARG has to be activated by other means. These may possibly include phosphorylation by kinases such as PKC or FAK, for instance (Chikumi et al, 2002;Disatnik et al, 2002;Suzuki et al, 2003;Dovas et al, 2006), as well as regulation of LARG homodimerization by CD98hc, which has long been known to regulate its activity (Chikumi et al, 2004). Further molecular investigations, in vitro, in cell culture should be performed to dissect this regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of oligomerization diminishes the in vivo GEF activity of Dbl (38) and abolishes ␤1PIX function in vivo (37). In the cases of p115RhoGEF, LARG, and PDZ-RhoGEF, deletion of the C-terminal parts that were required for oligomerization had no significant effect on the in vitro GEF activities but resulted in the drastic stimulation of in vivo functions (40,41). Taken together, these findings suggest that oligomerization may be an important common molecular feature in the GDP/ GTP exchanging reactions on the small GTPase, which are mediated by either some members of Rab5GEFs or RhoGEFs, albeit with fundamental differences in their physiological roles.…”
Section: Physiological Significance Of Als2 Homo-oligomerizationmentioning
confidence: 99%
“…These findings fuel speculation that the Rab5GEFs might function as a multiple protein complex in vivo, regardless of whether homo-or heterophilic complexes are formed. By contrast, several RhoGEFs, including ␤1PIX (36, 37), Dbl (38), RasGRF1 (39), Ras-GRF2 (39), p115RhoGEF (40,41), LARG (41), and PDZ-Rho-GEF (41), have already been shown to dimerize or oligomerize. Inhibition of oligomerization diminishes the in vivo GEF activity of Dbl (38) and abolishes ␤1PIX function in vivo (37).…”
Section: Physiological Significance Of Als2 Homo-oligomerizationmentioning
confidence: 99%
“…Furthermore, overexpression of LARG in acute myeloid leukemia (AML) has been shown to exhibit growth-promoting activity [78]. A number of studies show that LARG and its transforming potential can be activated by focal adhesion kinase (FAK) phosphorylation [80] and/or hetero-oligomerization through LARG's inhibitory C-terminal region [81]. Apparently, LARG-RhoGEF activity can be regulated by many different mechanisms in addition to its previously described role in Gα subunit signaling by GPCRs.…”
Section: Larg-mediatedmentioning
confidence: 99%